Pengeluaran Limbah Penebangan Hutan Tanaman Industri dengan Sistem Pemikulan Manual - Ahmad Budiaman; Agus Rahmat (Institut Pertanian Bogor (IPB University), 2009)
This paper presented result of the study on extraction of felling waste by manual bundling systems: assessment of qualitative performance The study is carried out at an Industrial Plantation Forest in South Kalimantan. Two bundling methods were apllied in this study, i.e. bundling by the use of net and rope. The results of the study showed that adaptation level of workers for the systems were good enough. The most mistaked work elements for both methods was compacting the waste for bundling, while the less mistaked work element was unload travel to the waste location.